Genetic engineering for enhanced production of a novel alkaline protease BSP-1 in Bacillus amyloliquefaciens - Jiang, Cong; Ye, Changwen; Liu, Yongfeng; Huang, Kuo; Jiang, Xuedeng; Zou, Dian; Li, Lu; Han, Wenyuan; Wei, Xuetuan (Frontiers in Bioengineering and Biotechnology, 2022)
Alkaline protease has been widely applied in food, medicine, environmental protection and other industrial fields. However, the current activity and yield of alkaline protease cannot meet the demand. Therefore, it is important to identify new alkaline proteases with high activity. In this study, we cloned a potential alkaline protease gene bsp-1 from a Bacillus subtilis strain isolated in our laboratory. BSP-1 shows the highest sequence similarity to subtilisin NAT (S51909) from B. subtilis natto. Then, we expressed BSP-1 in Bacillus amyloliquefaciens BAX-9 and analyzed the protein expression level under a collection of promoters. The results show that the P43 promoter resulted in the highest transcription level, protein level and enzyme activity. Finally, we obtained a maximum activity of 524.12 U/mL using the P43 promoter after fermentation medium optimization. In conclusion, this study identified an alkaline protease gene bsp-1 from B. subtilis and provided a new method for high-efficiency alkaline protease expression in B. amyloliquefaciens.